2020
DOI: 10.3390/s20082197
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared Spectroscopy for Monitoring Sternocleidomastoid Muscular Oxygenation during Isometric Flexion for Patients with Mild Nonspecific Neck Pain: A Pilot Study

Abstract: Since there is merit in noninvasive monitoring of muscular oxidative metabolism for near-infrared spectroscopy in a wide range of clinical scenarios, the present study attempted to evaluate the clinical usability for featuring the modulatory strategies of sternocleidomastoid muscular oxygenation using near-infrared spectroscopy in mild nonspecific neck pain patients. The muscular oxygenation variables of the dominant or affected sternocleidomastoid muscles of interest were extracted at 25% of the maximum volun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 66 publications
(127 reference statements)
0
2
0
Order By: Relevance
“…Figures 2 and 3 and Tables in Appendix A report the measured physiological and optical parameters. Apart from the preliminary characterization on a small group of subjects performed using a hybrid TD-NIRS/DCS system (Lindner et al 2016), the only SCM diffuse optical characterizations reported up to now have been performed by using FD-NIRS or CW-NIRS (Istfan et al 2021, Yang, Yang, Chen, Lai, Hu, Chang, Tu & Guo 2020, Van Hollebeke et al 2022, Katayama et al 2015, which have shown to be less reliable in measuring absolute values. Most studies report trends in blood oxygenation instead.…”
Section: Discussionmentioning
confidence: 99%
“…Figures 2 and 3 and Tables in Appendix A report the measured physiological and optical parameters. Apart from the preliminary characterization on a small group of subjects performed using a hybrid TD-NIRS/DCS system (Lindner et al 2016), the only SCM diffuse optical characterizations reported up to now have been performed by using FD-NIRS or CW-NIRS (Istfan et al 2021, Yang, Yang, Chen, Lai, Hu, Chang, Tu & Guo 2020, Van Hollebeke et al 2022, Katayama et al 2015, which have shown to be less reliable in measuring absolute values. Most studies report trends in blood oxygenation instead.…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, NIR spectroscopy has been successfully applied in agriculture [ 22 ], drug [ 23 ], foods [ 24 , 25 ], petroleum [ 26 ], textile [ 27 ], and environment [ 28 ]. And nowadays, NIR spectroscopy has been widely studied and applied for measuring biochemical parameters.…”
Section: Introductionmentioning
confidence: 99%